Penerapan Model PembelajaranProject Based Learning( Pjbl) Berbantukan MediaPembelajaran Komik Untuk Meningkatkan HasilBelajar Siswa Kelas X Sma Negeri 2 SukoharjoTahun Ajaran 2015/2016 - Casanah, Uswatun, Dr. Wafrotur Rohmah ,M.M (2016)
The purpose of this study was to determine whether the application of learning models Project Based Learning (PPA) can improve learning outcomes of economics in class X 3 SMA Negeri 2 Sukoharjo aran year 2015/2016. This study uses a Class Action Research (CAR), which held as much as the second cycle in which each cycle traversed by four stages, namely: (1) the action planning; (2) implementation of the action; (3) observing the action; and (4) reflection action. The subjects of this study were all students of class X 3 SMA Negeri 2 Sukoharjo 2015/2016 school year as many as 35 students with a composition of 21 women and 14 men. This research was carried out together with the teacher collaborator economic subjects. Data collection methods used are observation, testing, and documentation. The results showed an increase in student learning outcomes. It can be seen from the value of the average grade and mastery learning. Before the action implemented or pre-cycle values obtained an average of 55.86, in the first cycle of the average values obtained sebasar class 77.2 and the second cycle values obtained average grade of 84.57 So there is a rise in the average value of the prior cycle to the next first cycle to the second cycle. Completeness percentage of students in pre-cycle showed the number of 37, 14% (13 students completed the learning of all students, 35 students), in cycle 1 at 65.71% (23 students completed the learning of all students, 35 students) and in cycle 2 at 84.71% (30 students completed the learning of all students, 35 students). Based on this study, it was concluded that the implementation of Project Based Learning Method Learning berbantukan comic media in economic learning can improve learning outcomes economy.